Neill: from gretna green creed to summerhill experience - Santana, Elizabete Conceição (Revista Hipótese, 2017)
Assuming that the diaries reflect the thinking of teachers, it has been identified in A Domine Log dilemmas from which Alexander S. Neill built his pedagogic creed, in 1915. After demonstrating how this creed was consolidated, up to the establishment of Summerhill school in 1924, this paper is concluded by raising questions considering the need to study ways to take to the elementary public school systems innovations and practices based in Summerhill.